Cognitive Control and Ruminative Responses to Stress: Understanding the Different Facets of Cognitive Control - Zareian, Bita; Wilson, Jessica; LeMoult, Joelle (Frontiers in Psychology, 2021)
Rumination has been linked to the onset and course of depression. Theoretical models and empirical evidence suggest that deficits controlling negative material in working memory underlie rumination. However, we do not know which component of cognitive control (inhibition, shifting, or updating) contributes most to rumination, and whether different components predict the more maladaptive (brooding) versus the more adaptive (reflection) forms of rumination. We aimed to advance theory and research by examining the contribution of different facets of cognitive control to the level and trajectory of brooding and reflection. At baseline, participants completed three cognitive tasks that assessed their inhibition, shifting, and updating biases, respectively. Next, using experience sampling methodology, participants rated their level of rumination and negative affect nine times during the 48 hours after their most stressful exam. At each time point, higher levels of brooding, but not reflection, predicted higher levels of negative affect at the next time point. Furthermore, several facets of shifting and inhibition, but not updating, predicted brooding immediately after the exam and its trajectory of change over 48 hours. Additionally, difficulty inhibiting neutral words predicted both brooding and reflection. These findings inform theoretical models describing the role of cognitive control in brooding and reflection.